JURIDICAL REVIEW OF ARTICLE 112 OF THE REGULATION OF THE MINISTER OF AGRARIAN AFFAIRS/HEAD OF THE NATIONAL LAND AGENCY NUMBER 3 OF 1997 REGARDING THE LEGAL CONSEQUENCES OF THE POSITION OF THE EXECUTOR OF A WILL IN A DEED OF GRANT DUE TO A WILL IF THE EXE - Sari, Putri Nurmalita; Handayani , I Gusti Ayu Ketut Rachmi; Tuhana , Tuhana (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
A testamentary gift is a special testamentary stipulation, whereby the person who bequeaths to one or more persons gives certain items from their inherited assets or provides items of a certain type, such as, for example, all their movable or immovable items, or grants rights use the proceeds from all or part of his inheritance. According to the provisions of Article 112 paragraph (1) a point 3 letter b Regulation of the Minister of State for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 concerning Provisions for Implementing Government Regulation Number 24 of 1997 concerning Land Registration (PMNA/KBPN No.3/1997), states that "PPAT Deed regarding a gift made by the Executor of the Will on behalf of the grantor of the will as the implementation of the will whose execution is authorized by the Executor of the Will." This research aims to examine the position of the executor of the will in the deed of gift by will if the grantor of the will dies, as well as to analyze the legal consequences of the position of the executor of the will in the deed of gift by will if the executor of the will dies. The research method is normative juridical. The type of data used is secondary data. Data analysis techniques using deductive reasoning presented descriptively. The results of this research are: The position of executor of the will in the deed of gift because the will if the grantor of the will dies based on Article 112 paragraph (1) a point 3 letter b (PMNA/KBPN No.3/1997) its implementation will not end with the death of one of the parties (heir). Meanwhile, the legal consequences that arise if the executor of the will dies, namely the executor of the will (executor-testamentair) who dies will be replaced by another executor of the will, because the giver of the will (the heir) has the right to appoint one or more executors-testamentair with The goal is that if one is absent or dies, another will be replaced.